The Influence of Green Intellectual Capital and Green Innovation in Improving Financial Stability - Maharani, Puspita; Setiawan, Harry; Syahputri, Anggraini; Malini, Helma; Azazi, Anwar (Krisnadwipayana International Journal of Management Studies, 2024)
This research aims to understand how Green Innovation and Green Intellectual Capital contribute to the improvement of Financial Stability in consumer goods manufacturing companies listed on the Indonesia Stock Exchange, as well as to explore how Corporate Social Responsibility (CSR) acts as a moderating variable between independent variables and financial stability.The study makes use of SPSS software and the Moderated Regression analysis (MRA) techniques. The 104 companies that made up the research sample received cecondary data from financial and sustainability reports consumer goods industry manufacturing companies during 2021- 2023 period. These findings prove that financial stability is negatively influenced by green innovation, but positively Green Intellectual Capital (GIC). Impact of Green Innovation and Green Intellectual Capital (GIC) on increasing financial stability has not yet been demonstrated to be moderated by Corporate Social Responsibility (CSR).